Nigeria-South Africa Agricultural Trade Relations and Its Implications for Domestic Agricultural Production in Nigeria - Michael Ejike Meze; Ekene Ekemezie (Journal of Social Science and Economics (JOSSE), 2026)
This study examines the impact of Nigeria’s importation of textile fabrics and agricultural raw materials from South Africa on the agricultural sector output of Nigeria. Utilizing secondary quarterly time-series data spanning twenty-eight years (1996 to 2023), the empirical model expresses agricultural sector output (AGRT) as a function of textile fabric imports (TEX), agricultural raw material imports (AGRM), the real exchange rate (RER), real GDP growth (GDPG), and an institutional quality index (IQX). The analytical framework relies on the Autoregressive Distributed Lag (ARDL) bounds testing technique to accommodate variables with a mixed order of integration and evaluate both short- and long-run cointegrating vectors. The empirical results from the ARDL F-Bounds test establish a strong long-run relationship among the variables (F-statistic = 21.33, exceeding the upper bound critical value at 5%). In the long run, both textile fabric imports (β=0.4622, p<0.01) and agricultural raw material imports (β=0.0874, p<0.05) exert positive and statistically significant impacts on Nigeria’s agricultural output, suggesting that these imports provide essential intermediate inputs and value-chain linkages that complement domestic production. Conversely, short-run estimates reveal that textile imports are statistically insignificant, while the error correction term confirms that 16.36% of short-run disequilibrium is corrected annually toward long-run equilibrium. Diagnostic tests confirm the absence of serial correlation and heteroscedasticity, while CUSUM plots validate parameter stability. Consequently, the null hypothesis is rejected. The study concludes that while imported raw materials currently drive long-run sectoral growth, policymakers must implement targeted domestic capacity-building strategies to reduce vulnerabilities to external trade dynamics.